A phenomenological study of third culture kids’ perceptions of international school climate over time - White, Tressa L; Grooms, Linda D (American Journal of Education and Learning, 2023)
Over the past 20 years, the demand for international schools has increased worldwide, with expectations to sustain this momentum through the next decade. While these schools struggle with many of the same issues as others in the west, the different context in which they exist brings an additional layer that needs more understanding. This interpretative phenomenological study explored the experience of school climate over time through the lenses of third culture kids who attended the school at which they are now employed. Eight employees from one international school in Malaysia were selected and interviewed to explore school climate factors that impacted their lives as students, changes in school climate over time, and ways they now perpetuate that school climate as employees. Three themes emerged as influential factors of change to the school climate over time: (a) community through relationships, (b) school connectedness, and (c) diversity. The scope of the experiences of school climate development over time adds a unique perspective not found in previous literature and provides insight into aspects of school climate that leave a lasting impact on students. International school leaders can also gain insight into the importance of continually assessing school climate and the value of providing opportunities to build community through engaging experiences.